2008
DOI: 10.1002/fld.1955
|View full text |Cite
|
Sign up to set email alerts
|

Method of fundamental solutions for partial‐slip fibrous filtration flows

Abstract: SUMMARYIn this study a Stokeslet-based method of fundamental solutions (MFS) for two-dimensional low Reynolds number partial-slip flows has been developed. First, the flow past an infinitely long cylinder is selected as a benchmark. The numerical accuracy is investigated in terms of the location and the number of the Stokeslets. The benchmark study shows that the numerical accuracy increases when the Stokeslets are submerged deeper beneath the cylinder surface, as long as the formed linear system remains numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Such studies include, but are not limited to, numerical simulations of Maze et al [1], Hosseini and Tafreshi [2][3][4], Wang and Pui [5], Wang et al [6], Zhao and Povitsky [7], Przekop and Gradon [8] as well as the experimental work of Podgorski et al [9], Wang et al [10], and Shin and Chase [11]. Since the infancy of filtration theory about fifty years ago, fibers have always been assumed to be circular.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies include, but are not limited to, numerical simulations of Maze et al [1], Hosseini and Tafreshi [2][3][4], Wang and Pui [5], Wang et al [6], Zhao and Povitsky [7], Przekop and Gradon [8] as well as the experimental work of Podgorski et al [9], Wang et al [10], and Shin and Chase [11]. Since the infancy of filtration theory about fifty years ago, fibers have always been assumed to be circular.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of geometrical setup of the Stokes flow about spherical droplet touching a fiber solved with the BSM leads to elevated condition number of the matrix M caused by near-parallel vectors directed from Stokeslets to collocation points [1][2][3][4][5]. This requires allocation of Stokeslets close to the surface.…”
Section: Selection Of Stokeslet Allocation Schemementioning
confidence: 99%
“…In the past decades, boundary element methods (BEM) and its variant, Boundary singularity method (BSM), have proven their efficiency in numerous fields of computational physics including micro-and nano-scale Stokes flows about particles, fibers and their ensembles (Zhao and Povitsky [1][2][3][4] and Zhao [5]) and became more advantageous over traditional mesh-based methods (Wrobel [6]). BEM and BSM require optimization of allocation of boundary elements to reduce the computational time and increase solution convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have found that fluids flowing past fiber surfaces experience a slip which could reduce the flow resistance in a microscale channel. The slip phenomenon in porous media has been vastly studied in recent literatures (Zhao and Povitsky, 2009;Hosseini and Tafreshi, 2010;Chai et al, 2011;Hosseini and Tafreshi, 2011;Kirsh and Shabatin, 2015).…”
Section: Introductionmentioning
confidence: 99%